Developing a Model of Entrepreneurial Competencies to Enhance Entrepreneurial Performance (Architecture Image Studies, 2025)
This study sought to construct and validate a model of entrepreneurial competencies that fosters improved entrepreneurial performance. Data was collected from 150 SME leaders and analysed using the Structural Equation Modelling (SEM) technique. The results confirmed four of the six proposed hypotheses, establishing significant links where strategic competencies influence network and opportunity competencies, and network competencies influence opportunity competencies. Conversely, the hypotheses suggesting a direct influence of strategic and network competencies on overall entrepreneurial performance were rejected. The study concludes that strategic and network competencies do indeed enhance entrepreneurial performance, but they do so indirectly, with opportunity competency acting as a crucial mediator.